Local Stability of Coexistence Point for Trophic Interaction Dynamics - Pasand, M.M. Share (Journal of Applied Nonlinear Dynamics, 2026)
Existence and local stability of a coexistence point are investigated for a class of nonlinear polynomial differential systems. The studied dynamical system may be used to represent dynamics of species populations in a trophic food chain with n distinguished populations. The presented model incorporates stage structured population dynamics and captures both predation and competition phenomena. Local stability is studied via introducing a change of variables and then applying the Lyapunov direct method. An example is given for clarification. The investigated model, enhances the previously presented differential equations for population dynamics via incorporating competition and stage structures in the general predator-prey model.